THE MAIN TASKS OF FORMING SOCIAL COMPETENCES FOR SELF-DEVELOPMENT AND EDUCATION IN STUDENTS (Academicia Globe: Inderscience Research, 2023)
This article discusses the main tasks of forming social competences for students' self-development and learning.